PENELITIAN KEPUSTAKAAN TENTANG KONSEP KEBIJAKAN PUBLIK DARI MERRIL S. GRINDLE DAN KONSEP KEBIJAKSANAAN PUBLIK DARI HOORGOWERI - Ferid Nugroho (PUBLIKA: Jurnal Ilmiah Administrasi dan Kebijakan Publik, 2022)
Public Policy. According to Anderson in Public Policy Making published in 1984, public policy is a policy developed by government officials and agencies. The meaning of wisdom is a careful, clever and thorough nature in making decisions or solving problems. Wisdom should be the basis for state administrators in making policies so that what is made will make good for most or all of the people affected directly or indirectly. This research uses library research design. Meanwhile, Khatibah (2011) argues that library research is an activity carried out systematically to collect, process, and conclude data using methods/techniques of problems faced through library research. There is a clear difference between policy and wisdom. Policy etymologically comes from the word policy, while wisdom comes from the word wishdom. Every policy that is made does not necessarily contain elements of wisdom in the manufacturing process. Every policy made should be implemented wisely so that it does not harm and make an unfavorable impact on society. The community must be able to distinguish whether the policy made is wise or not in its implementation.